'Look girls, this is how you do it': Exploring the dependence of managers on their consultants. (6th July 2010) - Macdonald, Stuart
Managers often need advice: management consultants are quite capable of giving advice. This may seem like the most elementary of transactions, but it is actually fraught with difficulties occasioned by the nature of information. In consequence, it rarely occurs. Instead, managers tend to make do with the pre-packaged and neatly labelled information that is management method. They are keener than ever to hire management consultants, but to explain and legitimise management method. This can lead to the dependency of the manager on the consultant, dependency hidden by a prevailing myth that an information transaction has taken place, that the consultant really has told the manager what the manager wants to know.